The effects of running shoe longitudinal bending stiffness and midsole energy return on oxygen consumption and ankle mechanics and energetics: A systematic review and meta-analysis - Stephen, C. H. N.; Kelly, L. A.; Schuster, R. W.; Diamond, L. E. (Journal of Sport and Health Science, 2025)
Purpose We aimed to investigate the effects of running shoe longitudinal bending stiffness (LBS) and midsole energy return on running economy and ankle mechanics and energetics. Methods PubMed, Scopus, SPORTDiscus, Embase, CINAHL, and Web of Science were systematically searched for this meta-analysis. Crossover studies comparing the effects of running shoe LBS and/or midsole energy return on at least 1 of the following outcomes: running economy, ankle plantarflexion moment, work, power, or angular velocity were included. Results Of the 2453 studies screened, 48 were included (n=878). Results indicated that advanced footwear technologies (AFTs) significantly reduced oxygen consumption (standardized mean difference = -0.44, 95% confidence interval: -0.60 to -0.28), p<0.001) as well as peak ankle moments and positive/negative ankle work and power. However, neither LBS nor midsole energy return alone significantly affected oxygen consumption, ankle moments, positive and negative work, or positive power. The effects of AFTs were moderated by the training status and speed of the runner. The quality of evidence for all outcomes were low or very low for all outcomes except the effect of LBS on negative ankle work. Conclusion AFT may improve running economy by minimizing ankle moments, work, and power. The absence of significant independent effects of LBS and midsole energy return suggests that the benefits of AFTs arise from the interaction of these properties. Further research is necessary to understand the mechanisms for improved running performance in AFTs.